Integrasi Artificial Intelligence dalam Pendidikan Agama Kristen untuk Membangun Karakter Spiritual Generasi Alpha - Nofry J. Walangitan (DIDASKO: Jurnal Teologi dan Pendidikan Kristen, 2026)
The rapid development of Artificial Intelligence (AI) presents both opportunities and challenges for Christian Religious Education in fostering the spiritual character of Generation Alpha, who are growing up in a digital culture. This study aims to analyze the implementation of Artificial Intelligence in Christian Religious Education and to formulate an integration framework that remains oriented toward nurturing students' faith and character. The study employed a qualitative approach using a library research method through the analysis of relevant books, scholarly articles, and academic documents. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data collection, data reduction, data display, and conclusion drawing. The findings indicate that Artificial Intelligence contributes to adaptive learning by enabling personalized learning materials, providing timely feedback, expanding access to learning resources, and strengthening students' digital literacy. However, the use of Artificial Intelligence also poses potential risks, including technological dependency, reduced quality of teacher–student relationships, and weakened spiritual disciplines when not accompanied by adequate pedagogical and spiritual guidance. The novelty of this study lies in the formulation of an Artificial Intelligence integration framework grounded in Christian pedagogy, which positions technology as a learning tool while preserving the teacher's essential role as a spiritual mentor and model of faith. Therefore, the integration of Artificial Intelligence should be implemented ethically, critically, and responsibly through strengthening teachers' digital competencies and developing a Christ-centered curriculum that supports the spiritual growth and character formation of Generation Alpha.   Abstrak Perkembangan Artificial Intelligence (AI) menghadirkan peluang sekaligus tantangan bagi Pendidikan Agama Kristen dalam membentuk karakter spiritual Generasi Alpha yang hidup di tengah budaya digital. Penelitian ini bertujuan menganalisis implementasi Artificial Intelligence dalam pembelajaran Pendidikan Agama Kristen serta merumuskan kerangka integrasi yang tetap berorientasi pada pembentukan iman dan karakter peserta didik. Penelitian menggunakan pendekatan kualitatif dengan metode studi kepustakaan (library research) melalui analisis buku, artikel ilmiah, dan dokumen akademik yang relevan. Data dianalisis menggunakan model interaktif Miles, Huberman, dan Saldaña yang meliputi pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil sintesis menunjukkan bahwa Artificial Intelligence berkontribusi dalam menyediakan pembelajaran yang adaptif melalui personalisasi materi, umpan balik secara cepat, perluasan akses terhadap sumber belajar, serta penguatan kemampuan literasi digital. Di sisi lain, penggunaan Artificial Intelligence berpotensi menimbulkan ketergantungan pada teknologi, menurunkan kualitas relasi guru dan peserta didik, serta mengurangi pembiasaan disiplin rohani apabila tidak disertai pendampingan pedagogis dan spiritual. Kebaruan penelitian ini terletak pada perumusan kerangka integrasi Artificial Intelligence berbasis pedagogi Kristen yang menempatkan teknologi sebagai sarana pembelajaran, sementara guru tetap berperan sebagai pembimbing spiritual dan teladan iman. Dengan demikian, pemanfaatan Artificial Intelligence perlu dilaksanakan secara etis, kritis, dan bertanggung jawab melalui penguatan kompetensi digital pendidik serta pengembangan kurikulum yang berpusat pada Kristus guna mendukung pertumbuhan iman dan karakter Generasi Alpha.